Prisoner reentry programs : penetrating the black box for better theory and practice - Grommon, Eric L. (LFB Scholarly Pub., 2013)
Upon release from prison, individuals must manage a complex mix of interrelated challenges. Housing, employment, and substance abuse treatment have been identified as three of the most pressing dimensions of prisoner reentry. Grommon explores how these challenges interact and affect levels of relapse and recidivism. Housing and employment are important antecedents that shape participation in substance abuse treatment and relapse. In turn, these initial effects directly or indirectly influence recidivism. The findings highlight the need to further explore reentry challenges and lead to a number.